Cigarette availability and affordability among school-going adolescent smokers in Zambia: Results from the 2011 Global Youth Tobacco Survey - Catherine Luputa; Wingston Felix Ng’ambi; Cosmas Zyambo (International Journal of Noncommunicable Diseases, 2024)
Introduction: Cigarette smoking is a major cause of preventable disease and death globally. In several countries in sub-Saharan Africa, there is a dearth of knowledge on adolescent’s access to cigarette smoking despite cigarette access being a critical determinant of smoking initiation among adolescents. Objective: The objective of this study is to understand the availability and affordability of cigarettes among school-going adolescent smokers in Zambia. Methods: This study utilized the secondary data from the 2011 Global Youth Tobacco Survey done in Zambia. Logistic regression was used to obtain unadjusted ratios (uOR) and adjusted odds ratios (AORs) and 95% confidence interval (CI) to examine cigarette availability and affordability among adolescent smokers. Results: A total of 1857 adolescents were included in the analysis. Of these, 13.8% had tried smoking, 25.39% had not been refused sell of cigarettes due to age, 20.70% had obtained cigarettes through buying from a store, shop, or from katemba, 21.09% were not asked proof of age when buying cigarettes, and 25% were not refused the purchase of cigarettes due to age. In multivariate analysis, cigarette availability and affordability were associated with trying cigarette smoking (AOR: 7.74, CI: 1.24–50.88: AOR: 2.181, CI: 1.13–4.22). Conclusion: Cigarette availability and affordability were associated with an adolescent trying cigarette smoking. Adolescents in Zambia could buy cigarettes without being refused due to age or asked for proof of age. Cigarette availability and affordability among adolescents play a critical role in smoking initiation among them. There is a need to augment policy on protecting adolescents by demanding proof of age whenever the adolescents are buying cigarettes.